Properties of Malaysian Solid Coco-Lumber - M. Khairul; S. Abdul Hamid; K. Izran; A. W. Mohd. Jamil; M. K. Mohamad Omar; A. Khairul; H. Hamdan; A. K. Yanti; M. T. Emlee; M. I. Nasarudin; A. K. Razali; A. K. Azrena; A. L. Nurfaizah (International Coconut Community Journal, 2009)
Solid coco-lumber is relatively a new raw material in Malaysia’s furniture industry. However, different situations can be seen in the Philippines and Indonesia as they are actively producing and marketing coconut wood-based products. In this study, the physical and mechanical properties such as moisture content, basic density, Modulus of Rupture (MOR), Modulus of Elasticity (MOE), shear stress, compression parallel to the grain, thickness swelling and water absorption properties of Malaysian solid coco-lumber were determined. The solid coco-lumber was divided into inner and outer parts and were tested under two different conditions i.e. green and air-dry conditions. The study showed that the physical and mechanical properties of the air-dried outer part of the solid coco-lumber were 50% higher compared to the inner part under both conditions. The results proved that the properties of coconut wood tested are very useful to the emerging coco-lumber based furniture industry in Malaysia.